Students' Perception Of Using Social Media To Improve Their Vocabulary Mastery - Wisnu Wardana; Muhammad Sukirlan; Budi Kadaryanto (English Language Education Study Program, 2026)
This study aimed to investigate students’ perceptions of using social media to improve vocabulary mastery and to identify the vocabulary aspects that students perceived as most enhanced through social media use. The research employed a descriptive quantitative design involving 36 students of the English Education Study Program at Lampung University. Data were collected through a questionnaire consisting of 51 closed-ended items using a five-point Likert scale and were analyzed descriptively. The findings revealed that students generally held positive perceptions toward the use of social media for vocabulary learning, as indicated by an overall mean score of 4.07. Among the four dimensions examined, Usefulness obtained the highest mean score (4.18), followed by Engagement (4.10), Ease of Use (4.05), and Vocabulary Aspects (3.97). Students reported that platforms such as YouTube, Instagram, Facebook, and Spotify provided authentic language exposure, increased motivation, and created enjoyable learning experiences through multimedia content. They also perceived improvements in various vocabulary categories, particularly nouns and verbs, while acknowledging challenges related to the prevalence of informal language, slang, and abbreviations on social media. These findings suggest that social media serves as an accessible, flexible, and engaging supplementary tool for vocabulary development. In conclusion, students perceive social media as an effective medium for enhancing vocabulary mastery, supporting both independent learning and authentic language exposure. Therefore, educators are encouraged to integrate social media into vocabulary learning activities while providing appropriate guidance to ensure a balance between informal and formal language use.